Predictors of Long-Term Mortality in Medically Treated Patients With Chronic Heart Failure in Kosovo - Gani Bajraktari; Shpend Elezi; Pranvera Ibrahimi; Genc Abdyli; Artan Bajraktari; Arlind Batalli; Afrim Poniku; Frank L. Dini; Michael Y. Henein (Reviews in Cardiovascular Medicine)
Background: Heart failure (HF) is a complex clinical syndrome that is associated with high morbidity and mortality. The prognosis of chronic HF in Kosovo has never been objectively assessed and compared with other countries. Thus, this study aimed to investigate the long-term prognostic value of clinical and cardiac function parameters in predicting the mortality of patients in Kosovo with chronic HF. Methods: This study included 203 consecutive patients with chronic HF who were followed up for a mean of 86 ± 40 months. The primary outcome of the study was all-cause mortality. Results: During the follow-up period, there were 94 deaths (46.3%). Deceased patients were older (p < 0.001), commonly in New York Heart Association (NYHA) class ≥III (p < 0.001), had lower 6-minute walk distances (p = 0.014), higher prevalence of type 2 diabetes mellitus (T2DM) (p = 0.018), raised creatinine (p = 0.001), and lower hemoglobin (p = 0.004). Moreover, these patients often had left bundle branch block (p = 0.001), lower left ventricular (LV) ejection fraction (EF) (p < 0.001), larger left atrium (LA) (p < 0.001), lower lateral and septal mitral annular plane systolic excursion (MAPSE) values (p = 0.001 and p < 0.001, respectively), and tricuspid annular plane systolic excursion (TAPSE) (p = 0.009), reduced lateral systolic myocardial velocity (s’) (p = 0.018), early diastolic myocardial velocity (e’) (p = 0.011) and late diastolic myocardial velocity (a’) (p = 0.010) velocities, reduced septal e’ (p < 0.001) and a’ (p = 0.032) velocities, and had higher E/e’ (p = 0.021), compared to survivors. Multivariate analysis identified NYHA class ≥III (odds ratio (OR) = 5.573, 95% CI 1.688–18.39; p = 0.005), raised creatinine (OR = 1.027, 95% CI 1.006–1.047; p = 0.011), advanced age (OR = 1.069, 95% CI 1.011–1.132; p = 0.020), enlarged LA (OR = 3.279, 95% CI 1.033–10.41; p = 0.044), and left ventricular ejection fraction (LVEF) ≤45% (OR = 3.887, 95% CI 1.221–12.38; p = 0.022), as independent predictors of mortality. Conclusions: In medically treated patients with chronic HF from Kosovo, worse functional NYHA class, impaired kidney function, age, compromised LV systolic function, and enlarged LA were independently associated with increased risk of long-term all-cause mortality.